2013
DOI: 10.1104/pp.113.223560
|View full text |Cite
|
Sign up to set email alerts
|

Plastid Genome Instability Leads to Reactive Oxygen Species Production and Plastid-to-Nucleus Retrograde Signaling in Arabidopsis

Abstract: The plastid genome is highly conserved among plant species, suggesting that alterations of its structure would have dramatic impacts on plant fitness. Nevertheless, little is known about the direct consequences of plastid genome instability. Recently, it was reported that the plastid Whirly proteins WHY1 and WHY3 and a specialized type-I polymerase, POLIB, act as safeguards against plastid genome instability in Arabidopsis (Arabidopsis thaliana). In this study, we use ciprofloxacin, an organelle doublestrand b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 83 publications
(119 reference statements)
3
74
0
Order By: Relevance
“…CIP is an inhibitor of gyrase, an enzyme that in plants is active in both mitochondria and chloroplasts but not in the nucleus (Wall et al, 2004). Gyrase inhibition by CIP promotes double-strand breaks (DSBs), and mutants for genes involved in organellar HR-dependent repair are more sensitive to CIP than the wild type (Cappadocia et al, 2010;Rowan et al, 2010;Parent et al, 2011;Janicka et al, 2012;Miller-Messmer et al, 2012;Lepage et al, 2013). Seedlings of recG1-1, recG1-2, and of the corresponding wild-type lines were grown in the presence of CIP, and the ability to develop normal first true leaves was scored, as previously described (Parent et al, 2011;Miller-Messmer et al, 2012).…”
Section: Arabidopsis Plants Deficient In Recg1 Have Reduced Recombinamentioning
confidence: 99%
“…CIP is an inhibitor of gyrase, an enzyme that in plants is active in both mitochondria and chloroplasts but not in the nucleus (Wall et al, 2004). Gyrase inhibition by CIP promotes double-strand breaks (DSBs), and mutants for genes involved in organellar HR-dependent repair are more sensitive to CIP than the wild type (Cappadocia et al, 2010;Rowan et al, 2010;Parent et al, 2011;Janicka et al, 2012;Miller-Messmer et al, 2012;Lepage et al, 2013). Seedlings of recG1-1, recG1-2, and of the corresponding wild-type lines were grown in the presence of CIP, and the ability to develop normal first true leaves was scored, as previously described (Parent et al, 2011;Miller-Messmer et al, 2012).…”
Section: Arabidopsis Plants Deficient In Recg1 Have Reduced Recombinamentioning
confidence: 99%
“…These Whirly family proteins share a typical DNA-binding structure (Desveaux et al, 2002) and participate in the maintenance of organellar genomes. Recent work demonstrated that a double knockout of AtWHY1 and AtWHY3 results in chloroplast defects due to illegitimate recombination in the plastid genome (Maréchal et al, 2009;Lepage et al, 2013), and AtWHY1 and AtWHY3 appear to stabilize the plastid genome by repressing short-range rearrangements (Zampini et al, 2015). Structural analysis also indicated that AtWHY2 binding may stabilize mtDNA to favor accurate repair of DNA double-strand breaks (Cappadocia et al, 2010).…”
Section: Atwhy2 Alters Mtdna Copy Numbersmentioning
confidence: 99%
“…4A), why1why3polIb is characterized by a severe growth retardation phenotype, in addition to yellow variegation ( Fig. 4A; Parent et al 2011;Lepage et al 2013). why1why3reca1 triple mutants show severe growth retardation as well and display white variegation and leaf distortion ( Fig.…”
Section: Short-range Rearrangements Are Abundant In Organelle Genomesmentioning
confidence: 99%
“…Quantitative PCR analysis of RECA1 expression was performed as described previously for 21-d-old plants (Lepage et al 2013). Every reaction was carried out on biological and technical triplicates relative to the amplification of beta tubulin.…”
Section: Quantitative Pcr Analysis Of Reca1 Expression In Reca1 Mutantsmentioning
confidence: 99%